2015
DOI: 10.33364/algoritma/v.12-2.526
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Aplikasi Web Untuk Pengajuan Cuti Pegawai Secara Online

Abstract: Perkembangan teknologi sekarang ini membawa dampak yang baik bagi manusia, dalam hal ini khususnya bagi sebagian besar perusahaan, dimana teknologi dapat mempermudah kegiatan manusia. Salah satu implementasi teknologi informasi yang sangat banyak diterapkan pada perusahaan yaitu sistem informasi kepegawaian, dimana salah satu nya adalah aplikasi pengajuan cuti. Terdapat penelitian tentang pengajuan cuti pegawai, namun hasil penelitian tersebut belum menyediakan kesempatan bagi pegawai untuk mengajukan cuti sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
2
0
6
Order By: Relevance
“…This is in accordance with the results of interviews and triangulation of sources which stated that applying for leave can be done online anywhere and anytime. This research is supported by the results of research conducted by Syaripudin & Cahyana (2015) which stated that the process of applying for leave can be done anywhere and anytime as long as it is connected to the internet network, because Study permit is one of the features found in the E-Master application. Study permits are used by ASN if they want to continue their education to a higher level.…”
Section: Resultsmentioning
confidence: 61%
“…This is in accordance with the results of interviews and triangulation of sources which stated that applying for leave can be done online anywhere and anytime. This research is supported by the results of research conducted by Syaripudin & Cahyana (2015) which stated that the process of applying for leave can be done anywhere and anytime as long as it is connected to the internet network, because Study permit is one of the features found in the E-Master application. Study permits are used by ASN if they want to continue their education to a higher level.…”
Section: Resultsmentioning
confidence: 61%
“…Selain dari bagian kepegawaian, permasalahan juga muncul dari sisi karyawan. Karyawan tidak dapat mengetahui jumlah saldo cuti atau ijin yang dapat mereka gunakan (Syaripudin & Cahyana, 2015). Kesulitan saat pengajuan cuti atau ijin secara mendadak.…”
Section: Pendahuluanunclassified
“…Metodologi yang dipakai dalam pengembangan aplikasi ini adalah dengan menggunakan metode Unified Software Development Process. Aplikasi web untuk pengajuan cuti pegawai secara online yang dihasilkan dapat memberikan solusi bagi permasalahan yang ada untuk meningkatkan kinerja dan efisiensi waktu dalam kegiatan di bagian kepegawaian yaitu pengajuan cuti pegawai secara online [6].…”
Section: Tinjauan Pustaka a Tinjauan Pustakaunclassified